Incorporation of Hydroxytyrosol Alkyl Esters of Different Chain Length as Antioxidant Strategy in Walnut Oil Spray-Dried Microparticles with a Sodium Alginate Outer Layer - Gimenez-Castillo, B (ELSEVIER SCI LTD, 2022)
Omega-3 rich vegetable oils, such as walnut oil, are gaining interest because of their health benefits. Synthetized homologous series of hydroxytyrosol alkyl esters (HTEs) with different alkyl chain lengths (C4-C18) were incorporated in purified walnut oil (PWO) spray-dried microparticles, designed with Capsul (R) (C) as encapsulating agent and sodium alginate (SA) as outer layer (PWO-C/SA). The encapsulation efficiency (>87%) and Tg of PWO-C/SA microparticles were not affected by the HTEs. The incorporation of HTE-Cl 0 increased the melting point (185.0 +/- 1.3 degrees C), decreasing the formation of Dimers + Polymers (1.12 +/- 0.05% at day 35 of storage) and the crystallinity of the microparticles (>170 C). The highest stability of PWO-C (HTE-C10)/SA suggests a specific location of HTE-C10 at the oil:water interface. The SA layer delayed the release of fatty acids during in vitro digestion. The incorporation of HTEs of medium chain length can be a suitable strategy to protect unsaturated oils encapsulated by spray-drying.